SOSIALISASI DAN INTERNALISASI DALAM PEMBELAJARAN DRUM ANAK-ANAK (Studi Kasus Pengajaran Drum di Lembaga Kursus Musik West Brothers) - Indra Permana (Institut Seni Indonesia Surakarta, 2019)
ABSTRACTÂ This paper begins with an interest in seeing the musical abilities of children learners of non-formal institutions of West Brothers music course in playing the drum, where the children show